METODE PERUMUSAN TITEL PARTIJ ACTA DALAM AKTA NOTARIIL DITINJAU DARI KUHPERDATA DAN UNDANG-UNDANG JABATAN NOTARIS - Yonatan, I Gusti Nyoman (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
The Civil Code regulates that types of agreements based on their contents are divided into unnamed agreements and named agreements. The form of an agreement which is written in the form of a notarial deed must be in accordance with the Law on the Position of Notaries. The Civil Code and the Law on Notary Positions do not regulate the method of formulating partij acta notarial titles, thus giving rise to legal uncertainty. The purpose of this research is to find out and examine the correct way to formulate partij acta title formulations and the legal consequences for the strength of the evidence of notarial deeds where the formulation of partij acta title formulations does not match the contents of the deed. This type of research is normative legal research with a conceptual approach and a case approach. The conclusion of this research shows that the way to prepare a partij acta title is by writing down the subject of the agreement, the object of the agreement, and/or the type of legal act being agreed upon, and the legal consequences for the evidentiary strength of a notarial deed where the formulation of the title does not match the content of the deed is that the strength of the proof is degraded to private deed. Apart from that, legal acts regulated in the deed may become void or null and void by law.